2021
DOI: 10.1109/access.2021.3078300
|View full text |Cite
|
Sign up to set email alerts
|

A Single Phase, Single Stage AC-DC Multilevel LLC Resonant Converter With Power Factor Correction

Abstract: Single stage LLC resonant converters with inherent power factor correction are getting popularity in AC-DC converters due to its reduced size and weight. However, single stage topologies are usually less efficient in regulating the dc bus capacitor voltage pertaining to line and load transients. This paper proposes a multi-level flying capacitor based single stage AC-DC LLC topology to address the issue of voltage balancing of dc-bus capacitor and to reduce the voltage stress of the switching devices. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…A comparison study between the proposed bridgeless ac-dc single-stage topology, shown in Figure 1, and the three topologies proposed in articles [20][21][22] is summarized in Table 1. This comparison highlights the strengths of the proposed converter.…”
Section: Proposed Ac-dc Bridgeless Converter Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison study between the proposed bridgeless ac-dc single-stage topology, shown in Figure 1, and the three topologies proposed in articles [20][21][22] is summarized in Table 1. This comparison highlights the strengths of the proposed converter.…”
Section: Proposed Ac-dc Bridgeless Converter Topologymentioning
confidence: 99%
“…17,18 To overcome this problem, bridgeless ac-dc single-stage PFC topologies are proposed. 17,[19][20][21][22][23][24][25][26] The proposed bridgeless ac-dc single-stage PFC rectifier in Das et al 20 is based on an isolated single active bridge (SAB) converter. This converter features controlled dc-bus voltage with a unity power factor and acceptable input current THD.…”
Section: Introductionmentioning
confidence: 99%
“…This control technique works well to maintain almost constant DC-bus voltage throughout a wide range of line and load variations. Figure 36 shows the three-level flying capacitor LLC resonant converter [149]. The study by [150] presented a five-level cascaded LLC resonant converter; the design and analysis of the system were presented for use in energy storage systems (ESSs) or grid-connected applications.…”
Section: Multilevel Resonant Convertersmentioning
confidence: 99%
“…The researcher also analyzed the wide-adjustable-range LLC resonant converter used in lithium-ion battery LIB charger of a plug-in hybrid EV system PHEV [31]. Different scholars [32][33][34][35][36] have also proposed a hybrid of LLC converter with a three-level conversion approach. MLIs are used to alleviate voltage stress experienced by switching devices; they are also used to increase the power range of LLC resonant converter as reported by [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the conventional topologies for realizing resonant converters are half-bridge and full-bridge, and multilevel inverters are not favorable for high-frequency resonant inverters since modelling them for control design is difficult, particularly when using high-frequency switching modulation approaches. To eliminate the drawbacks associated with half-bridge [6], full-bridge [40], phase-shifted full-bridge [41], and threelevel [36] inverters integrated with resonant tank network, a five level multilevel inverter is introduced in this paper.…”
Section: Introductionmentioning
confidence: 99%